Persepsi Pengguna terhadap Penggunaan AI dalam Kehidupan Sehari-hari Pendekatan Technology Acceptance Model (TAM) - Sutrita Br Situmeang; Amelia Khairani; Rizkah Fadillah (Bulletin of Artificial Intelligence, 2025)
The development of Artificial Intelligence (AI) technology has brought significant changes to various aspects of daily life, including information search, digital services, education, and social interaction. The presence of AI provides convenience, speed, and efficiency in completing various activities. However, the level of acceptance and utilization of AI within society still varies, influenced by users’ perceptions of ease of use, perceived benefits, and trust in the accuracy of information generated by AI. This study aims to analyze users’ perceptions and levels of acceptance of AI usage in everyday life in Indonesia using the Technology Acceptance Model (TAM) approach. The research method employed is descriptive quantitative, with data collected through a five-point Likert scale questionnaire. The questionnaire was distributed online to 35 respondents who had experience using AI technology. The variables analyzed include Perceived Ease of Use (PEOU), Perceived Usefulness (PU), Attitude Toward Using (ATU), Behavioral Intention to Use (BI), and Actual Use (AU). The results of the validity test indicate that all questionnaire items are valid, with calculated r-values greater than the r-table value of 0.334, while the reliability test produced a Cronbach’s Alpha value of 1.03, indicating that the research instrument has a very high level of internal consistency. Descriptive analysis shows that the PEOU variable achieved a percentage of 65%, PU 78%, ATU 72%, AU 75%, and BI 68%. These results indicate that respondents generally have positive perceptions toward the use of AI, particularly in terms of perceived usefulness and ease of use. These positive perceptions influence users’ attitudes, intentions to use, and actual use of AI in daily activities. Therefore, this study demonstrates that AI is well accepted by users and has strong potential to effectively support everyday activities.